Goodnight moon - Brown, Margaret Wise, 1910-1952; Hurd, Clement, 1908-1988. (New York : Harper & Row, 1975)
Goodnight to each of the objects in the great green room: goodnight chairs, goodnight comb, goodnight air.
English version
AD 360
Accelerated Reader
Keywords: Bedtime -- Juvenile fiction; Rabbits -- Juvenile fiction; Stories in rhyme -- Juvenile literature; Moon -- Juvenile fiction